Insuficiencia jurídica del art. 182 del Codigo Organico Integral Penal lo cual viola el num. 18 del art. 66 de la Constitución - Chávez Manzanillas, Gonzalo Secundino (2015)
The honor and the honor is a fundamental right of all people, which is derived from its own dignity and therefore demand state protection from the consideration of the dignity of the human person. The honor and the honor involves personal acceptance and construction in the public imagination, and even in the legal superstructure of a moral quality linked to duty, virtue, merit, heroism; transcending the family, offspring and sexual behavior; which is reflected in the opinion, the fame or glory and in different public recognition ceremonies; and it produces material rewards or honors, as positions, jobs, income, wealth, inheritance, etc. The Constitution of the Republic of Ecuador has protected the right to dignity and honor. The good name and honor are constitutionally guaranteed rights of a fundamental nature, which involves not only for their protection can act directly based on the Constitution when it has place through the tutela, but who also own constitutional requirements of the obligation for the authorities to provide protection against arbitrary attacks which are the subject follows. But this is not respected in the Code of Criminal Integral, since there is no rule which guarantees the good name and honor. Sanctioned only if one is falsely attributed a crime. This rule does not penalize any statement designed to discredit, dishonor or disparage another person, such as the attribution of a defect or lack of morality, the accusations are receptadas in the public perception as outrageous or insults in word or deed; that harm the reputation, credit or interest of the victim. It is imperative under the Constitution, the State takes the protection mechanisms that are appropriate to ensure the effectiveness of the rights enshrined in the constitution, and this implies the need for various means of protection, alternative, concurrent or subsidiary of According to the assessment is made on the matter by the legislature. The influence exerted on the other a good man, a good reputation, brings huge social, economic and political benefits. The honor is generally regarded as the conscience of the value one's self, regardless of the opinions of others. Instead honor is more on reputation, is something external, it comes from the consideration and the judgment of those around us, has to do with the reputation and prestige that deserves our good behavior, regardless of the internal concept. One is the sense of honor and another is the external objective concept that others have and honor